Settlement of Village Head Election Disputes - Nurasikin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The simultaneous selection of village heads in all districts / cities is intended to avoid negative things in their implementation, village head elections simultaneously consider the number of villages and the ability of election costs charged to the district / city revenue and spending budget so that it is possible to carry out bumpy implementation as long as it is regulated in the District / City Regional Regulation. As a result of the implementation of the policy of Simultaneous Village Head Election, in this Law is regulated regarding the filling of the position of Village Head who quits and is dismissed before the expiration of the term. In accordance with the background, the problem is formulated as follows; The regulation of the authority of the Regional Head resolves the dispute over the results of the Village Head Election and the resolution of the dispute over the results of the village head election by the Regional Head. The type of research used is normative legal research, with the approach used is the approach of legislation. Based on the results of the research found that the granting of authority to the Regional Head in order to resolve disputes over the results of the village head election, will raise new problems, the problem is related to the authority of the Regional Head as an executive state institution that is limited to the authority to carry out the Law only, and also the authority to resolve disputes over the results of village head elections will potentially be objective and not independent, Considering that the Regional Head is a state power formed by a political party, so his authority to resolve disputes over the results of the election of the village head will be political and impure to uphold the law